Land tenure and natural resource management: a comparative study of agrarian communities in Africa and Asia - Otsuka, Keijiro; Place, Frank (International Food Policy Research Institute, 2001)
The devastating environmental effects of deforestation and the exploitation of other natural resources in the developing world have been well documented, yet their impact on local communities has received far less attention. This report looks at how land degradation and deforestation are being addressed at the local level, where households have experienced the reduction of farm size and the decline of natural resources. Through a comparison of Asia and Africa, the evolution of land tenure institutions within diverse cultural, natural, and policy environments is examined. Specific topics include the evolution of customary land tenure, the impacts of land tenure policies, and common property management. The editors conclude that the best strategy for managing land and forest resources lies in promoting the establishment of property rights and investment in the improvement of the natural resource base.